THE ROLE OF MOBILE TECHNOLOGIES IN ENHANCING FOREIGN LANGUAGE LEARNING IN SECONDARY SCHOOLS OF UZBEKISTAN (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The transformation of education through modern technology has significantly changed teaching methods worldwide. Mobile applications, once regarded as supplementary tools, have now become indispensable in language learning. In Uzbekistan, the digitalization of education is progressing rapidly, supported by the “Digital Education” program for 2022–2026. This initiative emphasizes the integration of information and communication technologies (ICT) in general education schools. In light of these developments, it is crucial to assess the effectiveness of mobile technologies in learning foreign languages, particularly English, in the context of secondary schools in Uzbekistan.